Modeling of concentration profiles of charge carriers in inhomogeneous epitaxial layers - Pavlysh, V.; Danchyshyn, I.; Korzh, R.; Dronyuk, M. (Видавництво Національного університету «Львівська політехніка», 2002)
The new approach to the construction of the microtechnology physical-technological models is proposed in the present work. This approach allows us to analyse the processes of the IC and hybride IC epitaxial, resistive and conductive structures growth and formation of their electrophysical and mechanical parameters. We elaborated the model describing charge carriers concentration profile of inhomogeneous epitaxial structures that were grown under different technological conditions.
Keywords: semiconductor; model; growth; electroconductivity